Concurrent use of methanol and ethanol for chain-elongating short chain fatty acids into caproate and isobutyrate. (15th March 2020) - Chen, Wei-Shan; Huang, Shengle; Plugge, Caroline M.; Buisman, Cees J.N.; Strik, David P.B.T.B.
Abstract: Microbial chain elongation (MCE) is a bioprocess that could utilise a mixed-culture fermentation to valorise organic waste. MCE converting ethanol and short chain fatty acids (SCFA; derived from organic waste) to caproate has been studied extensively and implemented. Recent studies demonstrated the conversion of SCFAs and methanol or ethanol into isomerised fatty acids as novel products, which may expand the MCE application and market. Integrating caproate and isomerised fatty acid production in one reactor system is theoretically feasible given the employment of a mixed culture and may increase the economic competence of MCE; however, the feasibility of such has never been demonstrated. This study investigated the feasibility of using two electron donors, i.e. methanol and ethanol, for upgrading SCFAs into isobutyrate and caproate concurrently in MCE Results show that supplying methanol and ethanol in MCE simultaneously converted acetate and/or butyrate into caproate and isobutyrate, by a mixed-culture microbiome. The butyrate supplement stimulated the caproate production rate from 1.5 to 2.6 g/L.day and induced isobutyrate production (1.5 g/L.day). Further increasing ethanol feeding rate from 140 to 280 mmol carbon per litre per day enhanced the direct use of butyrate for caproate production, which improved the caproate production rate to 5.9 g/L.day. Overall, the integration of two electron donors, i.e. ethanol and methanol, in one chain-elongation reactor system for upgrading SCFAs was demonstrated. As such, MCE could be applied to valorise organic waste (water) streams into a wider variety of value-added biochemical. Graphical abstract: Image 1 Highlights: Methanol and ethanol are concurrently used for upgrading short chain fatty acids. Feeding ethanol in methanol chain elongation improved the caproate production rate. Increasing ethanol feeding rate enhanced chain elongation of butyrate to caproate. Butyrate addition improved caproate production and induced isobutyrate production. Isobutyrate production continued even after stopping the butyrate feeding.